Graphene oxide influence in soil bacteria is dose dependent and changes at osmotic stress: growth variation, oxidative damage, antioxidant response, and plant growth promotion traits of a Rhizobium strain. Issue 5 (28th May 2022) - Lopes, Tiago; Cardoso, Paulo; Matos, Diana; Rocha, Ricardo; Pires, Adília; Marques, Paula; Figueira, Etelvina
Abstract: Climate change events, such as drought, are increasing and soil bacteria can be severely affected. Moreover, the accumulation of emerging pollutants is expected to rapidly increase, and their impact on soil organisms, their interactions, and the services they provide is poorly known. The use of graphene oxide (GO) has been increasing due to its enormous potential for application in several areas and it is expected that concentration in soil will increase in the future, potentially causing disturbances in soil microorganisms not yet identified. Here we show the effects that GO nanosheets can cause on soil bacteria, in particular those that promote plant growth, in control and 10% polyethylene glycol (PEG) conditions. Low concentrations of GO nanosheets did not affect the growth of Rhizobium strain E20-8, but under osmotic stress (PEG) GO decreased bacterial growth even at lower concentrations. GO caused oxidative stress, with antioxidant mechanisms being induced to restrain damage, effectively at lower concentrations, but less effective at higher concentrations, and oxidative damage overcame. Under osmotic stress, alginate and glycine betaine osmoregulated the bacteria. Simultaneous exposure to PEG and GO induced oxidative damage. Plant growth promotion traits (indole acetic acid and siderophores production) were increased by osmotic stress and GO did not disturb these abilities. In the context of climate change, our findings might be relevant as they can form the premises for the implementation of crop production methodologies adapted to the new prevailing conditions, which include the presence of nanoparticles in the soil and more frequent and severe drought.